Dampak Pandemi Covid19 terhadap Usaha Kurir Lokal di Kota Samarinda - Umi Azizah (EXERO : Journal of Research in Business and Economics, 2022)
The Covid-19 Pandemic has had an impact on various business sectors, one of them is in the field of courier services. This research aims to determine the impact of Covid-19 pandemic on the income of local couriers in Samarinda. The method used in this research is a qualitative method using descriptive analytical approach, verification, and exploratory. This research is also supported by library research. The type of data used is primary data and secondary data. During the Covid-19 pandemic, the income of local courier in the city of Samarinda has decreased. This is due to consumer concerns about the transmission of Covid-19 virus through couriers, The existence of PPKM policy that makes it difficult for couriers to be free to do their activities, as well as MSMEs that are empty of buyers, and competitiveness between couriers. In 2020 the decrease reached 70% from 2019. While in 2021 it began to increase by 30% from 2020. The decrease in income during the pandemic was responded by local courier businesses in the city of Samarinda by lowering shipping cost, increasing online promotions, especially in implementing health protocols to stop the spread of Covid19 virus through couriers, as well as increasing consumer loyalty.